Risk aversion energy management in the networked microgrids with presence of renewable generation using decentralised optimisation approach - Ghaemi, Sina; Salehi, Javad; Hamzeh Aghdam, Farid (IET renewable power generation, 2019)
Energy management problem is regarded as an important subject in the networked microgrids (MGs) based distribution system, where each entity possesses individual objectives. In this study, risk aversion energy management has been proposed for each MG and the distribution network (DN) in order to assess risks associated with uncertain sources. Conditional value at risk technique is utilised for including variability of profit to the objective function. In addition, this study investigates usefulness of possibility of power trading among MGs. For this aim, separate power line is considered between two different MGs besides of their power lines with DN. Power flow constraints are implemented to energy management formulation of each MG and DN as well. The proposed energy management problem is expressed based on stochastic linear programming. In this study, auxiliary problem principle decentralised approach is utilised to solve the optimisation problem in order to consider computer hardware limitations and privacy constraints. The recommended energy management approach has been applied to the IEEE 33-bus DN which is modified by MGs. Then, the effectiveness of providing power link between each two different MGs on the obtained profit has been evaluated under the both islanded and grid-connected modes of operation and various risk aversion parameter of entities.